Water Services Devolution in Kenya : Briefing Note to Support Effective and Sustainable Devolution of Water and Sanitation Services in Kenya - World Bank Group (World Bank, Washington, DC, 2015)
The overview over the next pages summarizes key themes and findings from on-going technical assistance provided to the Kenyan water sector by the Water and Sanitation Program (WSP) of the World Bank’s Water Global Practice. Kenya’s new Constitution (Constitution of Kenya 2010) came into effect in 2013, declaring water supply and sanitation services a basic right and devolving key water and sanitation functions to the county level. Key legislation, including the County Government Act of 2012 and the Urban Areas and Cities Act of 2011, have provided the framework for far reaching changes. As these changes took shape before and after the new constitution came into effect, WSP’s TA programs have been providing specific advice at the national level1 to align the sector’s legal and institutional frameworks to the new decentralized constitution. The engagement and support to counties to adopt the new frameworks has been stepped up substantially since mid-2013. This is evidenced by the progress of the transition process under the Transition Authority and Commission for the Implementation of the Constitution. This note seeks to briefly highlight priorities and practical suggestions to pursue those priorities in order to support counties as they navigate the process of devolution.